Risk management and simulation - Gupta, Aparna (CRC Press, Taylor & Francis Group, 2014)
The challenges of the current financial environment have revealed the need for a new generation of professionals who combine training in traditional finance disciplines with an understanding of sophisticated quantitative and analytical tools. Risk Management and Simulation shows how simulation modeling and analysis can help you solve risk management problems related to market, credit, operational, business, and strategic risk. Simulation models and methodologies offer an effective way to address many of these problems and are easy for finance professionals to understand and use. Drawing on the author's extensive teaching experience, this accessible book walks you through the concepts, models, and computational techniques.